Prevalence of antibiotic resistance genes of Escherichia coli at the pig slaughterhouses in the Mekong Delta - Ngo Van Thong; Nguyen Khanh Thuan; Bui Thi Le Minh (Veterinary Integrative Sciences)
The study was conducted to determine the antimicrobial susceptibility and antibiotic-resistance genes of Escherichia coli at the pig slaughterhouses in the Mekong Delta, Vietnam. A total of 60 samples were collected at the slaughterhouse in the Mekong Delta, including 24 feces, 24 carcasses, 8 floors, and 4 wastewater samples. The prevalence of E. coli in feces, wastewater, carcasses, and floor samples was 91.67%, 50.00%, 29.17%, and 25.00%, respectively. A total of 79 E. coli isolates were examined for antimicrobial susceptibility to 15 antibiotics using the disc diffusion method according to CLSI 2021 guidelines. E. coli strains were highly resistant to amoxicillin (83.54%), ampicillin (78.48%), streptomycin (63.29%), and florfenicol (63.29%). However, those E. coli strains were sensitive to amoxicillin + acid clavulanic and amikacin (97.47%), cefaclor (95.45%), cefuroxime (93.67%), and enrofloxacin (92.41%). The results showed that 96.2% of examined E. coli strains were resistant from one antibiotic to eight antibiotics, and the most frequent multidrug-resistance phenotype was amoxicillin + ampicillin + florfenicol + streptomycin (13.92%). The prevalence of antibiotic resistance genes (strA, sulII, qnrA, tetA, blaampC, blaTEM, and blaCTX-M) in E. coli was determined by PCR. The prevalence of strA, sulII, qnrA, tetA, blaampC, and blaTEM genes in E. coli strains was 75.67%, 72.97%, 75.67%, 83.78%, 91.89%, and 83.78% respectively; however, blaCTX-M gene was not detected. Therefore, the contamination of E. coli exhibiting antibiotic resistance in pig slaughterhouses should be controlled to prevent public health.